Inhibition of hedgehog signaling ameliorates hepatic inflammation in mice with nonalcoholic fatty liver disease. Issue 4 (18th December 2015) - Kwon, Hyunjoo; Song, Kyoungsub; Han, Chang; Chen, Weina; Wang, Ying; Dash, Srikanta; Lim, Kyu; Wu, Tong
Abstract : Hedgehog (Hh) signaling plays a critical role in liver development, regeneration, injury repair, and carcinogenesis. Activation of Hh signaling has been observed in patients with nonalcoholic fatty liver diseases (NAFLD); however, the pathobiological function and regulatory mechanism of hepatic Hh signaling in the pathogenesis of NAFLD remain to be further defined. This study was designed to examine the effect and mechanism of hepatic Hh signaling in high‐fat diet‐induced NAFLD by using pharmacological Smoothened (Smo) inhibitors (GDC‐0449 and LED225) and liver‐specific Smo knockout mice. Administration of Smo inhibitors to high‐fat diet‐fed wild‐type mice significantly reduced the numbers of activated macrophages and decreased the expression of proinflammatory cytokines (tumor necrosis factor‐α, interleukin‐1β, monocyte chemoattractant protein 1, and interleukin‐6) as assessed by F4/80 immunohistochemistry and quantitative reverse‐transcription polymerase chain reaction, respectively. The Smo inhibitors were noted to have variable effects on hepatic fat accumulation. Liver‐specific deletion of Smo also reduced macrophage activation and inhibited proinflammatory cytokine expression, while it did not significantly alter fat accumulation in the liver. Mechanistically, we found that activation of glioma‐associated oncogene 1 by Hh signaling in primary hepatocytes increased the production of osteopontin, which subsequently enhanced the macrophage‐mediated proinflammatory response through paracrine signaling. Conclusion: Hepatocyte Hh signaling can promote liver inflammation through osteopontin‐mediated macrophage activation; this mechanism importantly contributes to the progression of NAFLD . (Hepatology 2016;63:1155–1169)